The Effect of Fetal Stimulation on the Quality of Life of Pregnant Women and Fetal Heart Rate - Arista Apriani; Yunia Renny Andhikatias; Dheny Rohmatika; Ernawati; Megayana Yessy Mareta; Wijayanti; Deny Eka Widyastuti (P3M Universitas 'Aisyiyah Surakarta, 2023)
Pregnancy can have a positive or negative effect on a woman's life in her reproductive cycle. Evaluation of the quality of life of pregnant women can aim to improve the effectiveness of health services. Stress in the form of high anxiety in pregnant women can affect the pattern of fetal heart rate. The aim is to describe the effect of early stimulation of fetal growth and development on the quality of life of pregnant women and fetal heart rate. The research was carried out in September 2021 - May 2022 with locations in two Community Health Centers. Type of quasi-experimental research (before and after with control experiment design). The sampling technique was purposive with a total of 30 divided into two groups. Data analysis with ANACOVA. The quality of life score of the experimental group was 22.99 points higher than the control group (b = 22.99; 95% CI; 20.56 to 25.41; p < 0.001). Adjusted R2 = 95.2%. And the experimental group had a fetal heart rate score 0.14 points higher than the control group (b = 0.14; 95% CI; -0.03 to 0.32; p < 0.001). Adjusted R2 = 43.9% by controlling for the level of formal education and the score before treatment. The conclusion is that there is an effect of early stimulation of fetal growth and development on the quality of life of pregnant women and fetal heart rate.